Group Counseling Using an Islamic Integrative Transactional Analysis Approach - Fridameka, Fridameka; Darimis, Darimis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Islamic-Integrated Transactional Analysis Group Counseling model is an intervention approach that combines the principles of Transactional Analysis (TA) with Islamic spiritual values to create a comprehensive and culturally responsive counseling framework, particularly for Muslim students. Transactional Analysis, developed by Eric Berne, focuses on understanding human personality through three ego states—Parent, Adult, and Child—and examining how interpersonal transactions influence communication patterns, relationship dynamics, life scripts, and individual decision-making. However, when implemented in Islamic educational settings, TA requires integration with Islamic psychological and spiritual concepts to address the holistic nature of human development. This integration is carried out by aligning the ego states with the Quranic concept of nafs, which includes nafs ammarah (the self inclined toward evil), nafs lawwamah (the self that reproaches), and nafs muthmainnah (the tranquil self). Furthermore, Qur’anic communication principles—such as qaulan ma’rufa (kind words), qaulan layyina (gentle speech), qaulan sadida (truthful speech), and qaulan karima (noble words)—enhance the interpersonal aspects of TA within the group counseling context. This article employs a literature review method to analyze TA theories, group counseling dynamics, and Islamic values, synthesizing them into a unified integrative model. The findings indicate that Islamic-Integrated TA Group Counseling effectively enhances self-awareness, strengthens ego control, reduces unhealthy communication patterns (games), reconstructs maladaptive life scripts, and fosters healthy social interactions. The inclusion of spiritual values provides deeper meaning to the behavioral change process, resulting in more stable and meaningful personal development. This integrative counseling approach is highly relevant for school counseling and Islamic educational institutions as a strategy to cultivate emotionally healthy, spiritually grounded, and morally upright individuals.